2013
DOI: 10.1378/chest.12-0896
|View full text |Cite
|
Sign up to set email alerts
|

Corrected End-Tidal PCO2 Accurately Estimates PaCO2 at Rest and During Exercise in Morbidly Obese Adults

Abstract: Measurements of arterial blood gases are important in studies of ventilatory control during exercise and can give valuable information about the effi ciency of ventilation and gas exchange. To avoid the invasive procedure of placing arterial catheters for sampling arterial blood, partial pressure of end-tidal CO 2 (P etco 2 ) has been used as a noninvasive method to estimate Pa co 2 in young, healthy adults at rest and during exercise. [1][2][3][4] These studies have concluded that, although P etco 2 may sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…16 studies were identified as possibly relevant and underwent a full text critical appraisal, resulting in 8 exclusions. One study investigated exercise programs for Prader-Willi patients [ 14 ], 3 studies investigated pulmonary physiotherapy in the bariatric population [ 15 , 16 , 17 ], 1 publication appeared to be a case report [ 18 ], 1 was a research protocol [ 19 ], 1 article was only available in Swedish [ 20 ], and 1 article was only available in Spanish [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 studies were identified as possibly relevant and underwent a full text critical appraisal, resulting in 8 exclusions. One study investigated exercise programs for Prader-Willi patients [ 14 ], 3 studies investigated pulmonary physiotherapy in the bariatric population [ 15 , 16 , 17 ], 1 publication appeared to be a case report [ 18 ], 1 was a research protocol [ 19 ], 1 article was only available in Swedish [ 20 ], and 1 article was only available in Spanish [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Often, the end-tidal partial pressure of CO 2 (P ETCO 2 ) is used as a surrogate for P aCO 2 , as it can be easily acquired noninvasively using a breath-by-breath metabolic measurement system. However, multiple studies have shown inaccuracies between arterial blood-gas derived P aCO 2 and expired gas derived P ETCO 2 in patients with pulmonary gas-exchange abnormalities and increased alveolar dead space [21][22][23][24]. Therefore, care should be taken when using end-tidal values to infer P aCO 2 and calculate dead space ventilation.…”
Section: Pulmonary Gas Exchange and Ventilatory Efficiencymentioning
confidence: 99%
“…Further, individuals with obesity generally adopt a rapid and shallow breathing pattern to minimise the work of breathing, especially at higher ventilatory rates[108]. Despite the rapid and shallow breathing pattern, both arterial P CO 2 (or P ETCO 2 ) and V D /V T are generally within normal ranges during submaximal exercise[23, 108, 113,119,124]. Further, multiple studies have reported a normal V′ E -V′ CO 2 slope, even in morbid obesity, when compared to either non-obese control groups or normative values (table 1 and figure1)[6, 108,[125][126][127].…”
mentioning
confidence: 99%
“…In this regard, we recently showed that moderate weight loss of 8% (∼7 kg) reduced the percentage of respiratory muscle contribution to total body oxygen uptake (V′O 2 ) by 26%, which accounted for almost half of the reduction in V′O 2 [39]. Although ventilation is increased in obesity, when taking into account the increased oxygen uptake and carbon dioxide output, ventilation and the ventilatory response to exercise appear to be normal in otherwise healthy obese, morbidly obese, as well as obese patients with sleep apnoea [30,46,50,53] and arterial carbon dioxide tension is maintained within normal limits [54,55].…”
Section: Respiratory Function During Exercisementioning
confidence: 99%